Analysis of intrathyroidal cytokine production in thyroid autoimmune disease: thyroid follicular cells produce interleukin-1 alpha and interleukin-6. - Grubeck-Loebenstein, B; Buchan, G; Chantry, D; Kassal, H; Londei, M; Pirich, K; Barrett, K; Turner, M; Waldhausl, W; Feldmann, M (1989)
Cytokine production was studied in thyroid tissue from patients with Graves' disease, Hashimoto's thyroiditis and non-toxic goitre. The expression of interferon gamma, tumour necrosis factor alpha and beta, interleukin-1 alpha and beta, interleukin-6 and platelet-derived growth factor A chain was assessed by slot-blot analysis of the respective mRNA in freshly isolated tissue samples. All seven cytokines were detected in patients of all groups. Although the respective mRNA levels were, in general, higher in thyroid autoimmune disorders, this appeared to relate to the degree of the lymphocytic infiltration of the thyroid gland at the time of surgery. Purified thyroid follicular cells expressed high levels of interleukin-1 alpha and interleukin-6 mRNA and when established in primary culture, purified thyroid follicular cells from Graves' disease as well as non-toxic goitre produced interleukin-1 alpha and interleukin-6 bioactivity spontaneously. In the case of interleukin-1 this could be further augmented by addition of lipopolysaccharide to the thyroid follicular cell cultures. These results demonstrate that the lymphocytic infiltrate found in autoimmune and non-autoimmune thyroid disorders is associated with cytokine production. Additionally we have shown that intrathyroidal cytokine production is not restricted to thyroid-infiltrating mononuclear cells, but may also involve thyroid follicular cells both in vivo and in vitro. The cytokines produced by thyroid follicular cells may have an important role in stimulating autoantigen specific T cells in vivo as both interleukin-1 and interleukin-6 facilitate T cell activation.